SISTEM SOSIAL PERMAKULTUR DALAM SKALA MAKRO - Prasanti, Rahmadhita Widya; Setiawan, Bakti (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
Permaculture is known as a grassroots movement that focuses on various aspects, such as the design of human settlements both in urban and rural areas, diversification of agricultural systems, while improving the environment. In the concept of permaculture, nature and humans are important aspects that are the main concerns. In its journey, permaculture has become part of social innovation because of its ability to answer social challenges that occur while providing community welfare. However, the practice of permaculture and literature related to permaculture that currently exist are only focused on the home scale, although permaculture aims to produce productive landscapes, there has not been much literature found on the permaculture systems on a macro scale, especially discussing how to apply the permaculture social systems on a macro scale. This study was conducted using a literature review method with an integrative review, discussing what precondition are needed in developing a permaculture social system on a macro scale, based on literature of permaculture and social innovation. Then the results of this study are, we propose three new precondition needed to develop and ensure the sustainability of the permaculture social systems on a macro scale.